Policy Review and Regional Development in Disaster Mitigation (Case Study: 2004 Aceh Tsunami and 2011 Tōhoku Tsunami) - Latue, Philia Christi; Manakane, Susan; Rakuasa, Heinrich (PT. Riset Press International, 2023)
The geological location of Indonesia and Japan means that both countries experience frequent disasters. On December 26, 2004, Aceh, located on the northern tip of the island of Sumatra and the westernmost province in Indonesia, was hit by a tsunami that left 166,000 people dead or missing and 500,000 people displaced. While on March 11, 2011, the Great East Japan Earthquake and Tōhoku Tsunami with a magnitude of 9.0 occurred and resulted in approximately 15,800 fatalities and 220,000 displaced persons. This study uses a descriptive comparative study method by reviewing policies and regional development in disaster mitigation after the Aceh Tsunami (2004) and the Tōhoku Tsunami (2011) occurred. Policies related to disaster mitigation in Aceh show that tsunamis were never considered in urban planning before the 2004 Aceh Tsunami, while Japan has developed them since 1896 after the Great Meiji Sanriku Tsunami occurred. Existing disaster mitigation policies in Aceh's spatial planning have also not been implemented optimally and consistently. Japan's policies and regional development in disaster mitigation can be a lesson learned as Japan is considered worldwide as a model country in the field of tsunami preparedness and resilience.